Blended learning in badminton subjects - Laili Nabella Pebriani; Wasis Djoko Dwiyogo (Journal of Science and Education (JSE), 2022)
This study aims to determine the effect of blended learning on badminton learning. The method used in this study is the literature review method. Sources were obtained online with Google Scholar and books from 2018 to 2022. The results of the data search have been found by the authors, which are influenced by several factors. The biggest thing that influences this research is the limited facilities and infrastructure owned by students, but there is an increase resulting from several previous studies.